Navigating Diversity in Plural Indonesia: Problems and Prospects of Multicultural Literature for English Department Students - Akun, Andreas (Bina Nusantara University, 2022)
The research aimed to show the supposedly unquestionable national slogan ‘Unity in Diversity’. It still got severe challenges today, as proven by the rise of religious, political, and psychological underpinnings of intolerance surrounding the 2019 presidential election, politically dividing Indonesian into pros or cons of NKRI (Negara Kesatuan Republik Indonesia or The United Nations of Indonesia). This was a reader response research of EnglishDepartment students using short stories to gather their perspectives on the role of Multicultural Literature (ML).The short stories were taken from internationally recognized authors from Indonesia, the USA, Japan, France, China, and Egypt. Questionnaires and interviews were used to intensively collect the participants’ experiences and ideas. The results of the research show that diversity problems are identified, and solutions are proposed through the literary learning curriculum design and process. It also shows the need to promote multicultural literature practice for English department students. The mastery of Multicultural Literary Competence is finally proposed as one of the golden goals of Indonesian national education, where diversity is the true color of Indonesia to easilyequip graduates to become global citizens. Today’s interconnected, globalized world has required millennials to possess CQ (Cultural Quotient) regardless of their diverse background. This CQ can effectively be cultivated through multicultural literature in a multicultural education system. Only through mastering CQ cultivated through ML are Indonesian graduates ready to enter the global and digital competition as global citizens.